Teaching Developing Performance for Staff Members in University Of Khartoum According to (ISO 9002) Criteria's - Faisal Mohamed Abdul-Wahab; Yassir Mohammed Mahgoub (University of Science and Technology, Yemen, 2016)
Abstract: This study aims to know the point of view of the upper management of University of Khartoum, and Educational Department staff members (Foundations of Education - Educational Technology - Curriculum and Teaching Methods - Educational Psychology - Special Education - Sport Education - Art Education- and Pre- School Education) about their suggestions for developing academic and Professional performance in University of Khartoum in the light of (ISO 9002).       The study tried to answer the main question :(What is the Suggested vision for applying the total quality system for developing the professional and the academic performance of staff member of University of Khartoum based on (ISO 9002) quality criteria? , The researcher selected nine items out of the eighteen items of (ISO 9002).The study has nine branched questions.        The researchers used the descriptive analytical method and designed an open questionnaire from ten areas . The researchers selected an intended sample for the study so as to take their suggestions in this study .The study sample consisted of (44) university staff which represent (77.1 %) of the study community. The study reached many results and ten recommendations, and as depending on (ISO 9002) criteria to develop the performance quality of University of Khartoum Staff members , activating the cultural quality , developing of the educational environment, and training of the staff members continuesly.